Dynamic Analysis of Monopile-Type Offshore Wind Turbine Under Sea Ice Coupling With Fluid-Structure Interaction - Liu, Yingzhou; Shi, Wei; Wang, Wenhua; Li, Xin; Qi, Shengwenjun; Wang, Bin (Frontiers in Marine Science, 2022)
The interaction between vertical offshore wind turbine (OWT) and sea ice with fluid is a complex process including local and global crushing of ice fragments and vibration of OWT. It is crucial to study the ice resistance of OWT structures considering the fluid-structure interaction (FSI). This article investigates a complete process of dynamic sea ice-monopile OWT interaction considering soil-structure interaction (SSI) and FSI effects. A fully coupled dynamic collision model of sea ice and OWT incorporating with the explicit non-linear collision tool ANSYS/LS-DYNA is proposed. The simulated ice loads in this study is verified by different simulation methods and international static ice force standards closely related to ice dynamic characteristic parameters. Then, the dynamic response and damage of the OWT structure during ice-structure interaction are studied using the fully interaction model with FSI coupling. The simulated ice force can produce a significant vibration response in the structure coupling with FSI due to occurrence of ice-induced resonance in the ice velocity range of 2.5–3.5 cm/s. Finally, the effect of fluid on the sea ice-OWT interaction in the initial velocity collision of sea ice is analyzed. FSI coupling can cause a certain level of collision hysteresis, accelerate the failure of sea ice breaking and reasonably reduce the energy of the structure.